A new grading system based on magnetic resonance imaging in a mouse model of subarachnoid hemorrhage - Egashira, Yusuke (Stroke, 2014)
BACKGROUND AND PURPOSE: A grading system for experimental subarachnoid hemorrhage (SAH) that does not require animal euthanasia is currently unavailable. We proposed a new grading system based on magnetic resonance imaging (MRI), and evaluated the feasibility of this method in a mouse model of SAH. METHODS: SAH was induced by endovascular perforation in adult male C57BL/6 mice. Mice underwent MRI 24 hours after SAH, and were categorized into the following five grades based on T2*-weighted imaging: Grade 0, no visible SAH or intraventricular hemorrhage (IVH); Grade 1, minimal/localized SAH without IVH; Grade 2, minimal/localized SAH with IVH; Grade 3, thick/diffuse SAH without IVH; Grade 4, thick/diffuse SAH with IVH. Neurological deficits were then assessed and the mice euthanized for conventional SAH grading. RESULTS: Among a total of 47 mice, 4% were scored as grade 0, 30% as grade 1, 11% as grade 2, 30% as grade 3, and 36% as grade 4. This MRI grading had excellent interobserver reliability (weighted κ value = 0.94), and there were strong correlations between the MRI grading and the conventional grading (r = 0.85; P < 0.001), or between MRI grade and neurological scores (r = −0.46; P < 0.01). CONCLUSIONS: The new MRI grading correlated well with conventional grading, and enabled in-vivo evaluation of SAH severity. This grading system may offer advantages in future studies of experimental SAH.